3D‐Printed, All‐in‐One Evaporator for High‐Efficiency Solar Steam Generation under 1 Sun Illumination. Issue 26 (4th May 2017) - Li, Yiju; Gao, Tingting; Yang, Zhi; Chen, Chaoji; Luo, Wei; Song, Jianwei; Hitz, Emily; Jia, Chao; Zhou, Yubing; Liu, Boyang; Yang, Bao; Hu, Liangbing
Abstract : Using solar energy to generate steam is a clean and sustainable approach to addressing the issue of water shortage. The current challenge for solar steam generation is to develop easy‐to‐manufacture and scalable methods which can convert solar irradiation into exploitable thermal energy with high efficiency. Although various material and structure designs have been reported, high efficiency in solar steam generation usually can be achieved only at concentrated solar illumination. For the first time, 3D printing to construct an all‐in‐one evaporator with a concave structure for high‐efficiency solar steam generation under 1 sun illumination is used. The solar‐steam‐generation device has a high porosity (97.3%) and efficient broadband solar absorption (>97%). The 3D‐printed porous evaporator with intrinsic low thermal conductivity enables heat localization and effectively alleviates thermal dissipation to the bulk water. As a result, the 3D‐printed evaporator has a high solar steam efficiency of 85.6% under 1 sun illumination (1 kW m −2 ), which is among the best compared with other reported evaporators. The all‐in‐one structure design using the advanced 3D printing fabrication technique offers a new approach to solar energy harvesting for high‐efficiency steam generation. Abstract : An all‐in‐one solar steam generator with a concave structure (3D‐CG/GN) is prepared by using layer‐by‐layer 3D‐printing fabrication. High solar absorption, fast water transport, and excellent heat localization enable a high solar energy conversion efficiency of 85.6% under 1 sun illumination, which is among the best compared with other reported evaporators.